ANALISA PENDAPAT ULAMA TERHADAP BATASAN WAKTU DALAM WAKAF DAN AKIBAT HUKUMNYA - Kholid Masyhari (Universitas Wahid Hasyim Semarang, 2019)
Abstract Waqf is a good deed dedicated by waqif (the person who gives waqf) to his property to nadlir (administrators / recipients of waqf) so that the object can be used by the general public. After the waqf pledge was stated by waqif, then from that moment the ownership of the object was moved to Allah, meaning that the general public now has the right to benefit the object that is represented (mauquuf). The concept that is commonly understood by society as told by the jurists (jurisprudence experts) in some literacies, that waqf is holding back property and using it in the way of Allah, said Sayyid Sabiq in his Sunnah fiqh. On the other hand this opinion is reinforced by the hadith narrated by Ibn Umar whose hadith chunks state: